STRATEGI BAURAN PEMASARAN KOPI GUNUNG ARCA PADA KELOMPOK TANI MEKARWANGI JAYA - Danapriatna, Nana; Ismarani, Ismarani; Asyani Listyowati, Esi; Supah, Pela (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2023)
Mekarwangi Jaya Farmers Group is a coffee farmer group in Sukawangi Village, Bogor Regency which markets local specialty Bogor coffee in the form of dry beans and ready-to-brew coffee powder, but faces obstacles in marketing these coffee products. The purpose of this research is to determine the implementation of the 4P marketing mix for Gunung Arca Coffee, determine consumer assessments of the marketing of Gunung Arca Coffee and determine the priority marketing mix strategy for Gunung Arca Coffee in the Mekarwangi Jaya Farmer Group. This research uses primary and secondary data sources. Descriptive methods were used and Analysis Hierarchy Process (AHP) was used in this research to answer the research objectives. Based on the results of the analysis, it is known that the Mekarwangi Jaya Farmers Group has implemented the 4P marketing mix, namely product, price, promotion and distribution. Consumers feel that the quality of Gunung Arca Coffee is guaranteed, the price of Gunung Arca Coffee is affordable, media locations or promotional activities carried out by the Mekarwangi Jaya Farmers Group are easy to find, and the sales location for Gunung Arca Coffee is not strategic. The main priority marketing objective is to improve the business image with the first ranking marketing mix, namely product.